Short-term delayed effects of Kinesio taping on sprint cycling performance - Trecroci, A.; Formenti, D.; Rossi, A.; Esposito, F.; Alberti, G. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to assess short-term delayed effects of Kinesio taping (KT) on maximal cycling performance. A design with repeated measures was used. Fifteen healthy trained subjects underwent 3 conditions: no KT (without tape), KT (Kinesio tape applied longitudinally on the thighs), and sham taping (Kinesio tape applied horizontally on the thighs). Each subject performed 2 sets of 3 × 6-second sprints (separated by 3 minutes) interspersed by 30 minutes of rest on a cycle ergometer. Allometric scaling of peak power (PP) and average power (AP) values were computed and analyzed for each sprint performance. Both PP and AP decreased significantly after 30 minutes (between set 1 and set 2) in all conditions, with a greater decrease in no KT condition compared with KT and sham (p < 0.01). No significant differences were observed between KT and sham conditions. The application of KT on thigh muscles attenuated the performance decrease that occurred after 30 minutes of rest between the 2 sets compared with the no KT condition. This finding suggests athletes may use KT to better manage their performance during delays in competition events.